MEMBANGUN RESILIENSI ANAK: PERAN PASTORAL KONSELING TERHADAP KORBAN KEKERASAN SEXSUAL DI UPTD-PPAPROVINSI SULAWESI UTARA - Novita Pardamean Sianturi; Manambe, Claudia Vain; Harlinda Losoh Putri Agama; Mila Enjeli Salindeho (PT. Giat Konseling Nusantara, 2025)
Child abuse is an essential element in psychological recovery after sexual abuse. The study aims to review the role of counseling pastoral counseling in building signs of sexual abuse in uptd-ppa province of north sulawesi. The pastoral counseling approach creates a safe environment and provides emotional support for the victimized children, focusing on the restoration of their spiritual, emotional, and social aspects. Through guidance based on religious values, victims gain a better understanding of themselves and the strength to overcome trauma. The study involves a qualitative approach. Research shows that pastoral counseling interventions greatly contribute to raising children's self-esteem, alleviating anxiety, and building the necessary social skills to interact in society. Awakening consequences also help children overcome trauma and improve their quality of life. Thus, pastoral counseling plays a key role in the recovery of victims of sexual violence, emphasizing social and spiritual support on their journey of healing.